English medieval church towers : the Northern Province - Ryan, W. E. David (Boydell Press, 2018)
Diocese of Blackburn -- Diocese of Carlisle -- Diocese of Chester -- Diocese of Durham -- Diocese of Leeds -- Diocese of Liverpool -- Diocese of Manchester -- Diocese of Newcastle -- Diocese of Sheffield -- Diocese of Southwell and Nottingham -- Diocese of York.